Monitoring of Rice Dryer Machine Using Tray Dryer Method - Herani, Neneng; Rahmat, Saepul; Prasetia, Vicky (Infotekmesin, 2023)
Indonesia is an agricultural country with 40% of the population's livelihood provided by farmers. Harvested rice typically has a moisture content of 20-27% on a wet basis. The type of artificial dryer that is often used is the tub or rotary type. This research aims to develop a rice dryer using a combined tray and rotary-type method. Based on the result, the higher the speed dryer, the shorter the drying time. The net result of this test is that the relationship between time and engine speed is inversely proportional. The higher the speed, the shorter the drying time. The net result of this test is that the relationship between time and engine speed is inversely proportional. Rice drying results can be described as dry, but not including ready-to-eat rice standards. The higher the speed, the shorter the drying time.